2023
DOI: 10.1186/s13018-023-03797-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-345-3p is a potential biomarker and ameliorates rheumatoid arthritis by reducing the release of proinflammatory cytokines

Abstract: Objectives The study was to explore the influence of microRNA (miR)-345-3p on proinflammatory cytokines in patients with rheumatoid arthritis (RA). Methods A total of 32 RA patients and 32 healthy patients were enrolled. Proinflammatory factors in patients’ serum were detected by ELISA, and miR-345-3p was detected by RT-qPCR. The correlation between miR-345-3p expression and proinflammatory factors in RA patients was analyzed. The diagnostic value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…As a muscular tube for transporting oocytes and sperms, hydrosalpinx not only affect natural conception, but also signi cantly reduce the success rate of in vitro fertilization-embryo transfer (IVF-ET) [3][4]. Studies have shown that hydrosalpinx may interfere with embryo implantation by affecting endometrial receptivity [5][6][7]. The possible mechanisms include mechanical scour caused by uid re ux [8], toxic effects of hydrops on embryos [5,7,9], and effects of hydrops on endometrial receptivity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a muscular tube for transporting oocytes and sperms, hydrosalpinx not only affect natural conception, but also signi cantly reduce the success rate of in vitro fertilization-embryo transfer (IVF-ET) [3][4]. Studies have shown that hydrosalpinx may interfere with embryo implantation by affecting endometrial receptivity [5][6][7]. The possible mechanisms include mechanical scour caused by uid re ux [8], toxic effects of hydrops on embryos [5,7,9], and effects of hydrops on endometrial receptivity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that hydrosalpinx may interfere with embryo implantation by affecting endometrial receptivity [5][6][7]. The possible mechanisms include mechanical scour caused by uid re ux [8], toxic effects of hydrops on embryos [5,7,9], and effects of hydrops on endometrial receptivity [10][11][12]. In addition, enlarged uid can also affect ovarian function.…”
Section: Introductionmentioning
confidence: 99%